DETERMINATION OF ASSOCIATION CONSTANTS IN CYCLODEXTRIN DRUG COMPLEXATION USING THE SCATCHARD PLOT - APPLICATION TO BETA-CYCLODEXTRIN-ANILINONAPHTHALENESULFONATES - Sideris, EE; Valsami, GN; Koupparis, MA; Macheras, PE (PHARMACEUTICAL RESEARCH, 1992)
The appropriate Scatchard equation was developed for a system involving the formation of 1:1 and 1:2 substrate:cyclodextrin complexes. Simulation of this system was performed under the most common experimental conditions encountered in this type of study. The use of the equation allows for nonlinear least-squares estimation of the association constants. The interaction of the model compounds 1-anilino-8-naphthalenesulfonate (1,8-ANS) and 2(p-toluidinyl)-6-naphthalenesulfonate (2,6-TNS) with beta-cyclodextrin (beta-CD) was used to evaluate the theoretical model. Binding experiments were performed using either potentiometric titration or fluorimetric detection. The experimental data for 1,8-ANS/beta-CD fit well to the 1:1 binding model, with an association constant of 87 +/- 1 M-1. The association constants of the 1:1 and 1:2 2,6-TNS/beta-CD complexes utilizing direct potentiometry were 3737 +/- 6 and 149 +/- 2 M-1. It is shown that fluorimetry can give biased estimates for the association constants of the complexation 2,6-TNS/beta-CD, since the assumption of an equivalent quantum yield of bound species is not valid.
Keywords: ANILINONAPHTHALENESULFONATES; COMPLEXATION; cyclodextrins; DOUBLE-RECIPROCAL PLOT; FLUORESCENCE; ion-selective electrodes; SCATCHARD PLOT